Selection and optimization of contact materials for a hybrid system comprising an ito based photovoltaic cell and a BI₂TE₃/SB₂TE₃ thermoelectric module (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This study presents a detailed analysis of the selection and optimization of contact and interlayer materials for a hybrid energy conversion system that combines an indium tin oxide (ITO)-based photovoltaic (PV) cell with a thermoelectric (TE) module made of Bi₂Te₃/Sb₂Te₃. The main objective is to improve the overall energy efficiency of the hybrid structure by reducing contact resistance, enhancing heat transfer, and ensuring long-term reliability under thermal cycling conditions. To evaluate multilayer contact configurations such as Ni/Au, Ti/Ni/Cu, and Cr/Ag, the study employed realistic experimental parameters, along with ceramic interlayers composed of aluminum nitride (AlN) and aluminum oxide (Al₂O₃). The findings indicate that well-designed contact stacks can significantly minimize interfacial losses and thermal mismatch, achieving contact resistances as low as , while maintaining stable performance after 500 thermal cycles. Moreover, the hybrid PV–TE system demonstrated a notable improvement in total energy conversion efficiency, reaching approximately 9.1%, highlighting the synergistic contribution of both photovoltaic and thermoelectric components. Overall, this work provides practical design recommendations that can guide the future development of integrated PV–TE hybrid energy harvesting devices.
Keywords: electrical contact resistance; (ITO); Bi₂Te₃/Sb₂Te₃; interlayer engineering; (AlN); (Al₂O₃); thermal interface performance; reliability and stability testing; energy conversion efficiency